2020
DOI: 10.1111/pace.13920
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and cognitive impairment are predictive of takotsubo syndrome following pacemaker implantation

Abstract: BackgroundPacemaker (PM) implantation may cause acute emotional distress leading to takotsubo syndrome (TTS). Frailty and cognitive impairment are known to influence outcomes after surgical procedures. It is unclear whether they may also predispose to TTS following PM implantation.MethodsWe identified nine cases (81 ± 6 years) of TTS following PM implantation that took place between 2013 and 2017 in one high volume implantation center. TTS was diagnosed based on typical echocardiographic appearance with resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In almost all the articles included in our review, the only echocardiographic feature reported was the left ventricular ejection fraction (LVEF). In the most case it was in the normal range with few cases that presented a mild reduced LVEF, among the cases where it was reported the mean value was approximately 62% (range 50–75%) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In almost all the articles included in our review, the only echocardiographic feature reported was the left ventricular ejection fraction (LVEF). In the most case it was in the normal range with few cases that presented a mild reduced LVEF, among the cases where it was reported the mean value was approximately 62% (range 50–75%) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective analysis of a high-volume implantation center, Niewinski et al 7 identified nine cases of TTS following pacemaker implantation, with a prevalence of 0.54% on 1655 devices implanted between 2013–2017. In this study, female sex was not predictive of TTS, while cognitive decline and frailty syndrome were independently associated with the risk of TTS occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The Barcelona criteria were developed for patients with LBB block but have been successfully used in cases of AMI with an RV paced rhythm. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, acute emotional distress leading to Takotsubo syndrome is a rare but potential complication of pacemaker implantation that appears associated with frailty and cognitive impairment. 14,15 In the presence of cognitive impairment and frailty, specific preventive measures may be appropriate, such as avoidance of temporary transvenous pacing 16 and shortening of hospital stay, as usually done in device replacements. 17 Additionally, as shown in Fig.…”
mentioning
confidence: 99%